DETERMINATION OF HYDROTHERMAL ALTERATION STAGES OF AGHYOKHUSH GROUP AND MEREH DEPOSITS (LESSER CAUCASUS) - JAFAROV, Sultan Heybet; IMAMVERDIYEV, Nazim Ajdar (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Aghyokhush Group deposits are located on a morphogenetic junction of the volcano-tectonic-related fault systems of the Lesser Caucasus. The referred fault systems mostly consist of fault groups, sub-meridional faults, and north-sloping syn-volcanic, tectonic fault systems and thrusts directed from northwest to southeast. The geological structure of the Chovdar ore area is where, the Aghyokhush group and Mereh deposits are located on complex Middle and Upper Jurassic magmatic, metamorphic, and sedimentary rocks. The mineral assemblages and alteration zones observed in the Aghyokhush group and Mereh ore deposits are considered indicators for explaining the formation mechanism of mineralization. Methods. To be able to understand structural controls on ore mineralization, geological mapping, and chip sampling was done by AzerGold CJS's geologists. As a result, predictions were made on the location, lithological compound, alteration characteristics, size, and grade of potential ore bodies. Consequently, to examine the form and shape, the grade of potential orebody diamond drilling was carried out on a site, and core material from each drill hole was logged and sampled during the explanatory process. Results. The mineral assemblages and alteration zones observed in the Aghyokhush group and Mereh ore deposits are considered indicators for explaining the formation mechanism of mineralization. Tectonic discontinuities resulted in crushing and brecciation, which led to hydrothermally altered joints, planes, and ore mineralization over the discontinuities, which also, infrequently resulted in fault planes along the faults. Widespread rhyolite and rhyolite-dacite rocks in the ore field are mainly volcanogenic-sedimentary and volcanic, also, in some interval's subvolcanic facies. Mineralization phases caused alteration of the rock facies within deposits. Hydrothermal zoning was observed within altered rocks, that gradually changed from the margins to the center. The minerals identified are pyrite, chalcopyrite, pyrrhotite (rarely), marcasite, siderite, barite, quartz (vein and veinlets), vuggy silica, chalcedony, malachite, azurite, hematite, limonite, goethite, kaolinite, alunite, chlorite, epidote, calcite 2M mica, and sericite in Aghyohkhush group and Mereh deposits. As a result of the research, it is thought that the mentioned deposits are formed by the hydrothermal alteration of medium to felsic composed volcanic and subvolcanic rock facies, as a satellite deposits that are associated with Chovdar epithermal gold deposit. Conclusions. Discovered deposits are formed by the hydrothermal alteration of medium to felsic-composed volcanic and subvolcanic rock facies, as satellite deposits that are spatially and temporally associated with the Chovdar epithermal gold deposit. Deposits are formed by hydrothermal processes which lead to intermediate to high-sulfidation alteration characteristics on lithological units within the ore area. The mentioned alteration styles and structural controls that led to the discovery of deposits will be implemented in future exploration works that are going to be carried out on a Chovdar ore area.
Keywords: Aghyokhush group and Mereh ore deposits; Lesser Caucasus; hydrothermal alteration; intermediate to high-sulfidation porphyry-related epithermal deposits